Implementation of an Aggressive Enteral Nutrition Protocol and the Effect on Clinical Outcomes. (April 2017) - Yeh, D. Dante; Cropano, Catrina; Quraishi, Sadeq A.; Fuentes, Eva; Kaafarani, Haytham M. A.; Lee, Jarone; Chang, Yuchiao; Velmahos, George
Background: Macronutrient deficiency in critical illness is associated with worse outcomes. We hypothesized that an aggressive enteral nutrition (EN) protocol would result in higher macronutrient delivery and fewer late infections. Methods: We enrolled adult surgical intensive care unit (ICU) patients receiving >72 hours of EN from July 2012 to June 2014. Our intervention consisted of increasing protein prescription (2.0–2.5 vs 1.5–2.0 g/kg/d) and compensatory feeds for EN interruption. We compared the intervention group with historical controls. To test the association of the aggressive EN protocol with the risk of late infections (defined as occurring >96 hours after ICU admission), we performed a Poisson regression analysis, while controlling for age, sex, body mass index (BMI), Acute Physiology and Chronic Health Evaluation II (APACHE II) score, and exposure to gastrointestinal surgery. Results: The study cohort comprised 213 patients, who were divided into the intervention group (n = 119) and the historical control group (n = 94). There was no difference in age, sex, BMI, admission category, or Injury Severity Score between the groups. Mean APACHE II score was higher in the intervention group (17 ± 8 vs 14 ± 6, P = .002). The intervention group received more calories (19 ± 5 vs 17 ± 6 kcal/kg/d, P = .005) and protein (1.2 ± 0.4 vs 0.8 ± 0.3 g/kg/d, P < .001), had a higher percentage of prescribed calories (77% vs 68%, P < .001) and protein (93% vs 64%, P < .001), and accumulated a lower overall protein deficit (123 ± 282 vs 297 ± 233 g, P < .001). On logistic regression, the intervention group had fewer late infections (adjusted odds ratio, 0.34; 95% confidence interval, 0.14–0.83). Conclusions: In surgical ICU patients, implementation of an aggressive EN protocol resulted in greater macronutrient delivery and fewer late infections.